Analisis Keuntungan dan Kelayakan Usaha Pedagang Pengecer Buah di Kecamatan Banjarmasin Tengah - Nurul, Fadiya; Nasrudin, Nasrudin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This study aims to analyze the profits and feasibility of fruit retailers traders in the District of Central Banjarmasin. The data analysis technique uses profit analysis, revenue, and total cost calculation. Collecting research data obtained from interviews, questionnaires, and direct observation. Primary data was taken by the researchers through direct observation in the field and interviews with the respondents with the instrument in the form of a list of questions that had been compiled, while the secondary data was the result of a literature study. The population and sample of this study amounted to 37 traders with purposive sampling as the sampling technique.The results showed that retail fruit income in Banjarmasin Tengah District was Rp4.908.931 per month. The results of the feasibility test of retail fruit traders resulted in a BEP value of Rp5.593.812. In addition, the R/C value of the retail fruit trading business in Central Banjarmasin District is 1.32.